Advancing The Cardiovascular Care in Cancer Patients on Chemotherapy - Muhammad Yamin; Simon Salim; Muhammad Syahrir Azizi; Lusiani Rusdi; Aru Wisaksono Sudoyo; Anneira Amanda Putri (Interna Publishing, 2023)
Cardiotoxicity associated with chemotherapy, also known as Cancer Therapy-Related Cardiac Dysfunction (CTRCD), affects 10% of patients undergoing chemotherapy and is the most undesirable side effect of chemotherapy. Over time, it is anticipated that there would be an increase in the number of cancer patients receiving treatments that could harm their cardiovascular systems. Physicians should choose whether to continue, halt, delay, or reduce the dose of chemotherapeutic drugs to reduce the impact of cardiotoxicity. Cardiotoxicity screening and diagnosis need a variety of methods, primarily echocardiography to evaluate Left Ventricular Ejection Fraction (LVEF) and Global Longitudinal Strain (GLS). Depending on the clinical state, these procedures may be carried out prior to, during, or following chemotherapy. It's critical to reduce cardiovascular risk factors and offer advice on leading a healthy lifestyle before giving cancer patients medicines. There are a lot of cancer treatment facilities all around the world that don't have evidence-based perspective cardiotoxicity scores to stratify the risk of cardiovascular problems caused by cancer therapy. Additionally, comorbid conditions like diabetes and hypertension are frequently present in cancer patients, which can have a significant impact on clinical outcomes and cancer treatment. Therefore, this article aims to discuss assessment methods, clinical practice guidance, and prevention of CTRCD.